2015
DOI: 10.1038/ncomms9151
|View full text |Cite
|
Sign up to set email alerts
|

Learning-related representational changes reveal dissociable integration and separation signatures in the hippocampus and prefrontal cortex

Abstract: The episodic memory system enables accurate retrieval while maintaining flexibility by representing both specific episodes and generalizations across events. Although theories suggest that the hippocampus (HPC) is dedicated to represent specific episodes while the medial prefrontal cortex (MPFC) generalizes, other accounts posit that HPC can also integrate related memories. Here we use high-resolution functional magnetic resonance imaging in humans to examine how representations of memory elements change to ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

57
381
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 309 publications
(485 citation statements)
references
References 70 publications
57
381
8
Order By: Relevance
“…In particular, left anterior HPC showed greater functional connectivity during the early phase of learning with regions of mPFC, a finding predicted by SUSTAIN's neural framework (11). These results are also consistent with episodic memory findings that PFC biases encoding and retrieval of mnemonic information in HPC (9,27,28) and a recent proposal (29) that memories for individual experiences are updated through HPC-mPFC interactions to create generalized knowledge that supports complex behaviors like inference (8,30). We also found that early-learning HPC activation was coupled with regions implicated in a neural hierarchy of cognitive control along the rostral-caudal axis of lateral PFC (26,57,58).…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…In particular, left anterior HPC showed greater functional connectivity during the early phase of learning with regions of mPFC, a finding predicted by SUSTAIN's neural framework (11). These results are also consistent with episodic memory findings that PFC biases encoding and retrieval of mnemonic information in HPC (9,27,28) and a recent proposal (29) that memories for individual experiences are updated through HPC-mPFC interactions to create generalized knowledge that supports complex behaviors like inference (8,30). We also found that early-learning HPC activation was coupled with regions implicated in a neural hierarchy of cognitive control along the rostral-caudal axis of lateral PFC (26,57,58).…”
Section: Discussionsupporting
confidence: 79%
“…It is noteworthy that our findings were localized to the anterior portion of the HPC. Recent rodent (38) and human (8,54) evidence suggests episodic memories are encoded according to a gradient of generalization along the HPC anterior-posterior axis. Posterior HPC has been shown to exhibit distinct representations for individual episodes, whereas anterior HPC codes for integrated representations that generalize across related episodes (8,22,38,54).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies have demonstrated neural differentiation from learning of interrelated materials (Schapiro et al, 2012;Schlichting et al, 2015;Favila et al, 2016). The key contribution of the present work is that we provide a mechanism for differentiation (described above).…”
Section: Introductionmentioning
confidence: 99%